HUBUNGAN ASUPAN ZAT GIZI MAKRO TERHADAP STATUS GIZI PADA ANAK SD NEGERI REUSAK KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Amelia, Santi; Eka Putri, Suci; T.Muliadi; Mulyani, Itza (Universitas Cokroaminoto Palopo, 2025)
Nutritional status is a person's physical and health condition that is influenced by food intake and the use of nutrients in the body. Nutritional status can affect various nutritional problems that can occur in all age groups and can cause short-term/long-term health problems such as infectious diseases, obesity, obesity and other metabolic diseases. Good and optimal nutritional status is achieved when the body gets enough nutrients and is able to use them efficiently. Appropriate nutrient intake is essential to prevent disorders in growth and development, especially in school-age children. This study aims to analyze the relationship between macronutrient intake and nutritional knowledge on the nutritional status of children at Reusak Elementary School, Samatiga District, West Aceh Regency. The method used is a quantitative survey with a cross-sectional design, involving 73 students from grades IV, V, and VI. Data were collected through a questionnaire that assessed nutritional knowledge and a 2x24-hour food recall method that was not carried out consecutively to measure macronutrient intake. The results showed that the majority of respondents had normal nutritional status as many as 37 respondents, although the number of students who had abnormal nutritional status was not much different as many as 36 respondents. The results of the Chi-Square test show that there is a relationship between fat intake and nutritional status of 0.016. For the variables of carbohydrate and protein intake to nutritional status, there is no relationship (P =0,640) and (P = 0.366). So it is concluded that increasing nutritional knowledge and balanced macronutrient intake is very important to achieve optimal nutritional status in children. This study is expected to be the basis for further research and this study also recommends the need for a more intensive nutritional education program for students and parents to prevent nutritional problems in children.